On Some Coincidence Best Proximity Point Results - Naeem Saleem; Haroon Ahmad; Hassen Aydi; Yaé Ulrich Gaba (Journal of Mathematics)
In this paper, we discuss some (coincidence) best proximity point results for generalized proximal contractions and λ−μ-proximal Geraghty contractions in controlled metric type spaces. To clarify our study, various examples are given and some conclusions are drawn.